(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Electromagnetic radiation passes through matter there arises complicated phenomena which are analyzable in terms of statistically independent elementary interactions. Bach elementary process subdivides the energy of the incident photon. The radiation is thus progressively degraded in energy and deflected in various directions. The magnitude of each of these processes is given by the corresponding cross section. The cross section of these processes depend in turn on factors like the energy of interacting photon (E) and the atomic number of interacting material (Z). Considering the agent with which gamma ray interacts and the consequent result, the processes are classified in several groups.